Programmed and Non-Programmed Instruction: Integration Criteria in Curriculum Design. - Buckley, John W. (The Accounting Review, 1969)
This article particularly deals with matters related to teaching of accounting. A growing proportion of the "art of teaching" is yielding to the "science of teaching." One reason for the change in emphasis is the growing use of the systems approach for studying and proposing solutions to a wide range of organizational and social problems, a distinctive feature of which is to search for and relate interdisciplinary theories and techniques. The educational process lends itself to systems analysis. Learning theory now encompasses elements of many disciplines and coordinates these to produce improved learning experience. So far the curriculum designing is concerned, the first step is the identification of objective. Traditionally these objectives have been expressed in descriptive or uncooperative terms. Objectives of this type are vague and ambiguous, allowing for many possible interpretations of ends and means. They have little value when they are used as the only guideposts to learning.